Training trajectory of school music teachers: A case study in Lima-Peru - Cornejo Valdivia, Eugenia (2023)
This article presents the characterization of the training trajectory of music teachers from a private educational institution in Lima with the International Baccalaureate program, conducted in 2019. Using curriculum vitae formats and semi-structured interviews applied to ten full-time music department teachers, the proposed categories of initial and ongoing training were analyzed. The findings show that the training trajectories range between musical and pedagogical aspects. Initial training was mostly in music, while ongoing training was in pedagogy due to work-related reasons. Based on this information, different types of training trajectories are proposed. In addition, categories emerged about musical training and training in the development of the occupation that reveal ongoing training in non-formal spaces and in the workplace.